2014
DOI: 10.1002/fsn3.130
|View full text |Cite
|
Sign up to set email alerts
|

Determination of maize hardness by biospeckle and fuzzy granularity

Abstract: In recent years there has been renewed interest in the development of novel grain classification methods that could complement traditional empirical tests. A speckle pattern occurs when a laser beam illuminates an optically rough surface that flickers when the object is active and is called biospeckle. In this work, we use laser biospeckle to classify maize (Zea mays L.) kernel hardness. A series of grains of three types of maize were cut and illuminated by a laser. A series of images were then registered, sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…Also the mean VEV for the good milling hybrids (199.70 mm 3 ) was significantly (P < 0.01) larger than that of the poor milling hybrids (123.23 mm 3 ), whereas the mean FEV for the good milling hybrids (78.88 mm 3 ) was significantly (P < 0.01) smaller than that of the poor milling hybrids (101.91 mm 3 ). These results agreed with the higher proportion of vitreous endosperm found in good milling kernels (Weber et al, 2014). Similar results were obtained when Erasmus and Taylor (2004), after analysing 245 white maize kernels specifically bred for milling purposes using image analysis, found the endosperm percentages to vary between 46.3% and 63.7% (dry mass of vitreous endosperm divided by dry mass of whole kernel).…”
Section: Resultssupporting
confidence: 89%
“…Also the mean VEV for the good milling hybrids (199.70 mm 3 ) was significantly (P < 0.01) larger than that of the poor milling hybrids (123.23 mm 3 ), whereas the mean FEV for the good milling hybrids (78.88 mm 3 ) was significantly (P < 0.01) smaller than that of the poor milling hybrids (101.91 mm 3 ). These results agreed with the higher proportion of vitreous endosperm found in good milling kernels (Weber et al, 2014). Similar results were obtained when Erasmus and Taylor (2004), after analysing 245 white maize kernels specifically bred for milling purposes using image analysis, found the endosperm percentages to vary between 46.3% and 63.7% (dry mass of vitreous endosperm divided by dry mass of whole kernel).…”
Section: Resultssupporting
confidence: 89%
“…The majority of hybrids tested in the present study had flotation index over 56%, and according to Weber et al (2014), they are members of dent-type hybrids. The higher proportion of floating kernels implies lower hardness, vitreousness and breakage susceptibility (Peplinski et al 1992;Gaytán-Martínez et al 2006;Blandino et al 2010) and thus less nutritional value for poultry and pigs.…”
Section: And 4)mentioning
confidence: 63%
“…Polat et al [76] found that the application of fuzzy logic allowed them to determine more precisely the areas with contamination risks. Weber et al [77] observed that the fuzzy model applied to the determination of corn hardness yielded results that are more accurate.…”
Section: Discussionmentioning
confidence: 99%